Iran's expanding relations with China and their strategic dimensions - Dorraj, Manochehr (Emirates lecture series, 2013)
"In this paper the historical roots are analyzed, and the more recent political dynamics that shape the relationship, with a special emphasis on the post-1979 period; energy relations are examined, the sale of armaments, China's assistance to the development of Iran's nuclear program, trade relations, and political and strategic considerations that tie the two nations. In the context of the current political dynamics that govern this relationship, there is an attempt to shed light on how these dynamics impact the bilateral relations and the standing that both nations have with the United States. In this connection, China's position is examined on Iran's nuclear program, which epitomizes the delicate balancing act that Beijing is involved in, thereby hoping to maintain good relations with both antagonists--Iran and the United States. Finally, there is an analysis on the future direction of Iran-China relations."--Summary.